2011
DOI: 10.2169/internalmedicine.50.5725
|View full text |Cite
|
Sign up to set email alerts
|

Is Mild Renal Dysfunction a Risk Factor for Carotid Atherosclerosis in Apparently Healthy Adults?

Abstract: Objective Renal dysfunction may be related to cerebrovascular disease. The aim of this study was to assess the relationship between mild renal dysfunction and carotid artery atherosclerosis detected by ultrasonography in apparently healthy subjects. Methods A total of 2,106 persons (1,368 men and 738 women, mean age+/-S.D.: 56 +/-10 years) with no history of stroke were enrolled. Kidney function was evaluated in terms of estimated glomerular filtration rate (eGFR), calculated by using the relationship 194Cr -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Atherosclerosis has been regarded as the very important risk factor for the occurrence and development of cardiovascular and cerebrovascular disease [21]. Recently, different clinical indicators were used to predict atherosclerosis in order to evaluate the association of atherosclerosis with GFR decline, but results are quite inconsistent [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atherosclerosis has been regarded as the very important risk factor for the occurrence and development of cardiovascular and cerebrovascular disease [21]. Recently, different clinical indicators were used to predict atherosclerosis in order to evaluate the association of atherosclerosis with GFR decline, but results are quite inconsistent [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a comparative study, Takahashi et al [7] demonstrated that there was little association of renal dysfunction with early carotid atherosclerosis in apparently healthy adults, but that traditional vascular risk factors, such as aging and hypertension, appeared to play a major role. Similarly, a cross-sectional study conducted by Han et al [8] in 852 healthy individuals with age over than 30 years showed that aging was a major risk factor contributing to GFR reduction and that there was no independent correlation seen between the decline of GFR and atherosclerosis in a population with normal renal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study of apparently healthy Japan adult subjects showed that renal dysfunction is associated with early-stage carotid atherosclerosis (4). The participants of the present study were described as healthy individuals; however, the basal characteristics of the patients should be clearly defined, particularly with respect to the renal functional status.…”
mentioning
confidence: 79%
“…In addition, chronic kidney disease (CKD) appears to be a predictor of asymptomatic cerebral infarction and/or large vessel disease, as previously described (4,5). In this study, we primarily intended to clarify the significance of the risk components for arteriosclerosis in various sites based on the National Cholesterol Education Program-Adult Treatment Panel III criteria.…”
mentioning
confidence: 95%